Full bridge converter with reduced voltage stress and zerovoltage switching for LED based lighting application - Sreenivasulu Meda; Ramakrishna Busharaju; Narendra Rao Rajaboyana (Institute of Advanced Engineering and Science, 2026)
Light emitting diodes (LEDs) have emerged as an energy efficient lighting source in lighting industry. However, LEDs are current controlled devices and they require efficient driver circuits to illuminate uniformly. This research work presents a full bridge-based converter to drive multiple LED lamps. In the proposed topology, two different direct current (DC) input sources are connected in anti-series across the full bridge, which significantly reduces voltage stress on the switches. Zero-voltage switching (ZVS) is achieved using a single inductor, which minimizes switching losses and improves efficiency. The converter powers three LED lamps, in which two are identical lamps. In each leg of full bridge configuration, two inductors with different current magnitudes are connected to diminish current stress of conducting device. Additional advantages include low power processing, high efficiency, pulse-width modulation (PWM) dimming, driving multiple lamps, and reduced component count. A detailed theoretical analysis of the converter’s operating modes is provided to explain its performance and behavior. The concept is validated using numerical simulations with a total power rating of 60 W to validate the steady-state operation.